9 EXPRESSION PROFILES AS PREDICTORS OF BRONCHOPULMONARY DYSPLASIA IN EXTREMELY LOW GESTATIONAL AGE NEWBORNS. (1st March 2006) - Cohen, J.; Sun, Y.; Van Marter, L.; Leviton, A.; Allred, E.; Kohane, I.
Abstract : Background: Approximately half of all infants born before the 28th week of gestation develop bronchopulmonary dysplasia (BPD). Inflammatory regulators appear to be involved in the development of BPD both antenatally and postanatally. Postnatal factors contributing to BPD include hyperoxia, hypoxia, infection, patent ductus arteriosus, oxygen toxicity, and barotrauma from mechanical ventilation. Objective: To evaluate to what extent RNA expression profiles in umbilical cord tissue distinguish between infants who do and do not develop BPD. Study Design/Methods: Flash-frozen pieces of umbilical cord were available from 21 infants born before gestational age 28 weeks who developed BPD (defined as oxygen dependent at 36 weeks postmenstrual age) and from 34 of their peers who did not develop BPD. RNA extraction and microarray hybridization were performed at the core laboratory at Children's Hospital Boston. Results: Infants who developed BPD had decreased umbilical cord expression of mitochondrial membrane, energy metabolism (oxidative phosphorylation, citric acid cycle), RNA synthesis, and DNA repair gene sets. These genes were also expressed at lower levels in those with the lowest gestational age. We are not yet able to distinguish gestational age correlates from insult/response contributions to BPD pathogenesis. Conclusions: Expression profiles evident at the time of birth provide a meaningful window into the physiologic development of extremely low gestational age newborns. Expression profiling is likely to help identify pathways that contribute to the evolution and development of BPD.